The house of magical sounds [videorecording (DVD)] - Abbado, Daniele; Julia, Raul (Kultur, 2007)
Portrays the life and career of Claudio Abbado, the director of the Berlin Philharmonic, exploring his early influences, using animation and excerpts from rehearsals and concerts to demonstrate how a score becomes a musical performance.